A study on derivation method of motion feature points in sports motion analysis for racket matching - Sekine, N.; Takehara, S.; Kawano, T.; Suzuki, K. (Journal of Biomechanical Science and Engineering, 2020)
n this study, as part of efforts to assist beginners in sports such as tennis and badminton in selecting the most suitable equipment, an index for objectively evaluating such equipment is proposed. To accomplish this, standard swing trajectory variations are used to create an index from the viewpoint of human motion control. We begin by noting that human body data gained via motion capture are large in number because of the wide variety of equipment types used and due to the significant diversity of human body characteristics. Hence, even though motion capture devices are often used to capture swing motions, the most suitable human body segments for use in equipment evaluations have not yet been clarified. To facilitate this, it is necessary to reduce the overall number of body segments under consideration. In this paper, the method of deriving the feature points in sports motion was examined. More specifically, in order to obtain fundamental findings, tennis stroke and badminton smash motions are used as representative movements, and experiments using a motion capture device are performed. In the motion analysis that follows, we then investigate which markers can most clearly express the relationship between the racket and the human body in order to capture stroke motion characteristics. Then, an index of contribution is adapted to tennis swing and badminton smash motions, the motion feature points in the stroke and smash motion are derived, and the significant markers for motion analysis are identified and discussed.